A Genetically Encodable Ligand for Transfer Hydrogenation. Issue 17 (26th April 2013) - Mayer, Clemens; Hilvert, Donald
Abstract: Simple tripeptides are shown here to be versatile ligands for iridium‐catalyzed transfer hydrogenations affording large acceleration effects. A water‐soluble iridium complex with Gly‐Gly‐Phe, for example, catalyzes the reduction of diverse ketones, aldehydes, and imines by formate with turnover frequencies rivaling or outperforming those of established ligand systems. Regioselective reduction of coenzyme NAD + to NADH illustrates the potential utility of this system for biotechnological applications. Because peptides are genetically encodable, they represent an attractive class of foldamer ligands for creating artificial metalloenzymes. Abstract : Simple tripeptides are shown to be effective ligands for iridium‐catalyzed transfer hydrogenations. Peptide–iridium complexes efficiently reduce ketones, aldehydes, imines, and NAD + under mild conditions in aqueous buffer. As genetically encodable foldamers, peptides are attractive ligands for the construction of artificial metalloenzymes for diverse biotechnological applications.